Optimal control strategies for grid-assisted green hydrogen generation systems based on PEM technology: production and energy storage applications - Barbosa, Michael Feliphe da Silva (2024)
Dissertação (mestrado) - Universidade Federal de Santa Catarina, Centro Tecnológico, Programa de Pós-Graduação em Engenharia de Automação e Sistemas, Florianópolis, 2024.